2017
DOI: 10.3389/fcvm.2017.00016
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nanoparticles As Contrast Agents for the Functional and Molecular Imaging of Abdominal Aortic Aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is a degenerative disease of the aorta common in adults older than 65 years of age. AAA is usually imaged using ultrasound or computed tomography. Molecular imaging technologies employing nanoparticles (NPs) have been proposed as novel ways to quantify pathological processes, such as inflammation, within AAAs as a means to identify the risk of rapid progression or rupture. This article reviews the current evidence supporting the role of NP-based imaging in the management of AAA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Nanoparticle-based PGG delivery can be employed to quantify inflammatory events in vascular tissue pathologies such as AAA, atherosclerosis, etc. 43 Vyavahare et al . have used PGG-laden nanoparticle delivery extensively in small animal models.…”
Section: Current Issues With Pgg Administrationmentioning
confidence: 99%
“…Nanoparticle-based PGG delivery can be employed to quantify inflammatory events in vascular tissue pathologies such as AAA, atherosclerosis, etc. 43 Vyavahare et al . have used PGG-laden nanoparticle delivery extensively in small animal models.…”
Section: Current Issues With Pgg Administrationmentioning
confidence: 99%
“…Many AAAs remain asymptomatic and only incidentally undergo detection through abdominal imaging such as ultrasonography, computed tomography angiography, and magnetic resonance imaging ( 1 ). Despite many efforts to establish predictive or diagnostic imaging techniques ( 5 ), circulating biomarkers ( 6 ), or disease features such as intraluminal thrombus (ILT) ( 7 ) for indication of rupture-prone aneurysms, none have proven to be sufficiently robust to be implemented in clinical practice. No medical approaches to reducing AAA expansion have been validated, rather, once an aneurysm diameter has reached an established “threshold” [4.5–5.0 cm for women and 5.5 cm for men ( 8 )], the only treatment option involves surgical repair.…”
Section: Introductionmentioning
confidence: 99%
“…In associated human studies, USPIO- enhanced MRI has also been reported to enable successful visualization of severe inflammation within AAAs. The authors reported that patients with significant mural uptake of USPIO had a threefold higher AAAs growth rate (measured over 6 months) compared to those with no or non-specific USPIO uptake 33 . Degradation of elastic fibers was related to the development of the aneurysm.…”
Section: Discussionmentioning
confidence: 99%